Zacharie 12,10 relu en Jean 19,37 - Manns, F. (Liber Annuus, 2006)
Abstract The Pontifical Biblical commission published an important document “The sacred Scriptures of the Jewish people are a fundamental part of the Christian Bible”. A manifestation of the link between the two Testaments to their beginnings is the acceptance by Christians of the Sacred Scriptures of the Jewish people as the Word of God. The Church has accepted as inspired by God all the writings contained in the Hebrew Bible as well as those in the Greek Bible. This relationship is also reciprocal: on the one hand, the New Testament demands to be read in the light of the Old, but it also invites us to a “re-reading” of the Old in the light of Jesus Christ. In the Gospel of John many texts of the Old Testament are quoted and presented as fulfilled. The author studies the difficult text of Za 12:10 beginning with the critical problems of the Old Testament versions. The main versions are examined (HT, LXX, Peshitto). The precedent studies of Reim, Evans, Braun and Menken are also considered. In Judaism, re-readings were commonplace. The Old Testament itself points the way. The Books of Chronicles are a “re-reading” of the Book of Genesis and the Books of Samuel and Kings. What is specific to the Christian re-reading is that it is done in the light of Christ.